Effects of organosolv pretreatment using ethylene glycol on degraded empty fruit bunch for delignification and fractionation. Issue 1 (March 2020) - Chin, DWK; Lim, S; Pang, YL; Lim, CH; Shuit, SH
Abstract: Malaysia and Indonesia are the largest palm oil producers worldwide. In palm oil production, approximately one tonne of empty fruit bunch (EFB) will be generated as waste for every one tonne of palm oil produced. Currently, these fresh EFB are still underutilised and generally disposed under open environment. The fresh EFB are more susceptible to microbial attack under natural environment when exposed even for short period and become degraded empty fruit bunch (DEFB) which have lower quality. Consequently, disposal of DEFB becomes an enormous challenge as well as its following environmental problems including soil pollution and emission of greenhouse gases such as methane. However, DEFB remain as a promising lignocellulosic biomass feedstock with huge potential for production of high value added products entailing biofuels, bio-polymer and membrane with appropriate pretreatment. Therefore, DEFB was subjected to organosolv pretreatment in this research to recover its cellulose content. DEFB was discovered to possess higher cellulose content, lignin content and lower hemicellulose content as compared to fresh EFB. Organosolv pretreatment successfully fractionated DEFB to recover the cellulose portion by removing the lignin and hemicellulose content. Pretreatment with 50 v/v% ethylene glycol in the presence of 3 v/v% NaOH removed 75.1 wt.% lignin and 81.5 wt.% hemicellulose with 90.4 wt.% cellulose recovery. Furthermore, the cellulose purity of treated DEFB was improved drastically from 55.9% to 84.5%. For pretreatment liquor, the recoverable lignin was amounted to 74.6 % at pH 2.0. This study proved that organosolv pretreated DEFB exhibited the desirable properties for subsequent processes such as hydrolysis to synthesise the biomass waste into other high value added bio-products.